2004
DOI: 10.1111/j.1523-1755.2004.00464.x
|View full text |Cite
|
Sign up to set email alerts
|

Protease inhibitors modulate apoptosis in mesangial cells derived from a mouse model of HIVAN

Abstract: Oxidative stress seems to play a role in the accelerated rate of HTrMC apoptosis both under basal and MSS. Saquinavir may be inhibiting HTrMC apoptosis by mitigating oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
(43 reference statements)
1
11
0
Order By: Relevance
“…Morphine has been reported to cause kidney cell injury in both in vitro and in vivo studies [7], [8], [9], [10], [11], [12]. In the current study, we observed that administration of morphine contributed to albuminuria which appeared to be glomerular in origin and a consequence of the loss of slit diaphragm integrity [27].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Morphine has been reported to cause kidney cell injury in both in vitro and in vivo studies [7], [8], [9], [10], [11], [12]. In the current study, we observed that administration of morphine contributed to albuminuria which appeared to be glomerular in origin and a consequence of the loss of slit diaphragm integrity [27].…”
Section: Discussionsupporting
confidence: 56%
“…Morphine has been reported to exert a bimodal effect on the growth of kidney fibroblasts and glomerular mesangial cells [6], [7], [8], [9], [10]. Intravenous opiate addiction has also been considered a risk factor for the development of human immunodeficiency (HIV)-associated nephropathy [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…In an accompanying article in this issue of Kidney International Mongia et al [1] demonstrate viral-independent antiapoptotic and ROS-scavenging effects of PIs on mouse mesangial cells in vitro. This protection extends to the exaggerated mesangial apoptosis induced by HIV gene expression and recreational drug metabolites.…”
mentioning
confidence: 98%
“…The basis of this protection is complex, as both HIV reverse-transcriptase inhibitors and HIV protease inhibitors (PIs) have biologic actions independent of their antiviral effects. A new study by Mongia et al [1] in this issue of Kidney International shows that the PI saquinavir significantly blocks reactive oxygen species (ROS) generation and ROS-linked apoptosis in mouse mesangial cells independent of HIV gene expression. Thus, HAART modulation of renal injury may transcend its antiviral effects.…”
mentioning
confidence: 99%
“…Interestingly, mesangial cells harvested from HIV-1 transgenic mice showed both accelerated rate of proliferation as well as of apoptosis [38]. Since antioxidants were able to inhibit these growth characteristics of mesangial cells, these pro-mitogenic and pro-apoptotic effects of the HIV-1 transgene were attributed to the levels of ongoing oxidative stress [38]. …”
Section: Hiv-1 Proteins Have a Bimodal Growth Effect On Mesangial Cellsmentioning
confidence: 99%